Forest-associated bee species persist amid forest loss and regrowth in eastern North America. (August 2021) - Smith, Colleen; Harrison, Tina; Gardner, Joel; Winfree, Rachael
Abstract: Forest-associated species, which depend on forest habitat for their survival, are among the world's most vulnerable species due to widespread forest loss. However, in many parts of the world, forests are re-growing. Thus, if forest-associated species can persist in young forests their conservation outlook is less bleak. We examined the effects of forest loss and regrowth on bee pollinators in eastern North America using three datasets totaling 36, 605 individual specimens. First, we conducted a regional-scale study to identify forest-associated and habitat generalist bee species. Second, we examined how the abundance and richness of each group change with forest area and age, by collecting bees from forests chosen to vary orthogonally in these variables. Lastly, we examined whether the results of our field studies were consistent with long-term, regional trends in the richness of both groups, using a dataset of museum specimens collected between 1872 and 2011, which was a period of reforestation in our study region. We found that the abundance and richness of forest-associated bees increase with forest area, while being relatively insensitive to forest age. By contrast, habitat generalist bees are unaffected by forest area, but decrease in abundance with forest age. Consistent with these results, we found a 16% increase in the richness of forest-associated bees over a 140-year time series as reforestation occurred in eastern North America, but no significant trend for habitat generalists. Overall, our results show that the loss of forest area from a landscape harms forest-associated bees, and that young forests have high conservation value for both forest-associated and habitat generalist bees.